PEMAHAMAN HAKIKAT SAINS PADA GURU DAN SISWA SEKOLAH DASAR - Adi, Yogi Kuncoro; Widodo, Ari (Universitas Muhammadiyah Magelang, 2018)
The nature of science has not been taught as a teaching material at school in Indonesia. This study aims to reveal the understanding of teachers and primary students about the nature of science. This study was a survey research with descriptive approach. Data were collected through closed questionnaires for teachers and students. Teachers and primary students as research subjects were located in Kuningan District. Purposive sampling was used as a sample. The results showed that both teachers and students have an understanding of the nature of science in the range of Intermediate categories. Because of the importance of understanding about the nature of science in science subjects, it is expected that further research to develop materials and learning models based on the nature of science in primary school.